Spinoza and Other Heretics : the advantures of immanence - Yovel, Yirmiyahu (Princeton University Press, 1989)
This ambitious study presents Baruch Spinoza (1632-1677) as the most outstanding and influential thinker of modernity-and examines the question of whether he was the "first secular Jew." A number-one bestseller in Israel, Spinoza and Other Heretics is made up of two volumes-The Marrano of Reason and The Adventures of Immanence. Yirmiyahu Yovel shows how Spinoza grounded a philosophical revolution in a radically new principlethe philosophy of immanence, or the idea that this world is all there is-and how he thereby anticipated secularization, the Enlightenment, the disintegration of ghetto life, and the rise of natural science and the liberal-democratic state. In The Adventures of Immanence, Yovel discloses the presence of Spinoza's philosophical revolution in the work of later thinkers who helped shape the modern mind. He claims it is no accident that some of the most unorthodox and innovative figures in the past two centuries-including Goethe, Kant, Hegel, Heine, Marx, Nietzsche, Freud, and Einstein-were profoundly influenced by Spinoza and shared his view that immanent reality is the only source of valid social and political norms and that recognizing this fact is necessary for human liberation. But what is immanent reality, and how is liberation to be construed? In a work that constitutes a retelling of much of Western intellectual history, Yovel analyzes the rival answers given to these questions and, in so doing, provides a fresh view of a wide range of individual thinkers.